THE LINGUISTIC STATUS OF THE SEMANTIC FIELD AND LEXICAL-SEMANTIC GROUP - Tashlanova Nigora Djurayevna (Western European Studies, 2024)
This article discusses the study of a dialect layer of the Russian vocabulary of colour, which refers to historical-lexicological, as well as a dialectal colouration dictionary, considering in terms of composition, structural connections, and dynamics. The traditional lexical study is performed on semantic fields and lexical-semantic groups.
Keywords: dialect layer; study of dialect colourative dictionary; dynamics; lexicology